The doctoral research abstracts Vol:3 2013 / Institute of Graduate Studies, UiTM - Universiti Teknologi MARA, Institute of Graduate Studies (Institute of Graduate Studies, 2013)
Foreword: Congratulations to the 25 doctorates whose achievements we proudly celebrate in this 78 UiTM’s momentous convocation ceremony. This convocation may have marked the end of your highest scholarly achievements however it is the beginning of a new experience in enhancing execution of work from a wider perspective gained from this journey. One may also viewed it as a stepping stone for better things to come. To capture the novelty of your research, Institute of Graduate Studies has published another issue of the Doctoral Research Abstracts ranging from the discipline of science and technology, business and administration, to social science and humanities. We sincerely wish you all the best and may the Almighty guide you to a path of excellence and success. As you leave the university as alumni we hope a new relationship will be fostered between you and the faculty in bringing UiTM to greater heights. / Dato’ Sri Prof Ir Dr Sahol Hamid Bin Abu Bakar , FASc Vice Chancellor Universiti Teknologi MARA